1997
DOI: 10.1007/s000110050208
|View full text |Cite
|
Sign up to set email alerts
|

Tissue injury in neutrophilic inflammation

Abstract: The exudation of neutrophils is the hallmark of a form of inflammatory response occurring after tissue colonization by invading bacteria or as an expression of various non-infectious diseases. All these diseases are characterized by a high risk of developing irreversible tissue injury. Neutrophil-endothelium interactions, activation-induced functional and structural changes of responding neutrophils, regulatory systems of neutrophil function, and oxidative-proteolytic pathways responsible for histotoxicity are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
149
0
7

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(159 citation statements)
references
References 103 publications
2
149
0
7
Order By: Relevance
“…Because tumors typically have very poorly developed blood vessels and have regions of hypoxia, 24 small areas of necrosis may arise and produce chemotactic factors for neutrophils, which can in turn generate IL-8. 32 Our IL-8 experiments using MN-11 tumors suggest that an influx of neutrophils is associated with necrosis. Thus, both events can occur: necrosis may recruit neutrophils and neutrophils may produce additional chemoattractants.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Because tumors typically have very poorly developed blood vessels and have regions of hypoxia, 24 small areas of necrosis may arise and produce chemotactic factors for neutrophils, which can in turn generate IL-8. 32 Our IL-8 experiments using MN-11 tumors suggest that an influx of neutrophils is associated with necrosis. Thus, both events can occur: necrosis may recruit neutrophils and neutrophils may produce additional chemoattractants.…”
Section: Discussionmentioning
confidence: 80%
“…For example, interleukin-8 (IL-8), a potent chemoattractant for neutrophils of the C-X-C type, 32 has been shown in glioblastoma. 33 IL-8 has also been identified in human gastric, colorectal and bronchioloalveolar carcinomas 34 -36 and in B-cell chronic lymphocytic leukemia.…”
Section: (Am J Pathol 2000 156:509 -518)mentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophils in the airways undergoing necrosis in situ are a major source of DNA, which makes CF sputum so tenacious [5]. The excessive accumulation of activated neutrophils in the lungs can lead to lung damage [6]. Proinflammatory chemoattractants have been found to be elevated in bronchoalveolar lavage fluid (BAL) from CF, including IL-8, IL-1, IL-6 and tumour necrosis factor alpha (TNFa) [7], leukotriene B 4 (LTB 4 ), complement factors, such as C5a, and bacterial products also act as potent chemoattractants for neutrophils [2].…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophil elastase (NE) is a major secretory product from activated neutrophils and is a major contributor to tissue destruction in inflammatory diseases such as acute respiratory distress syndrome (ARDS), lung emphysema, and rheumatoid arthritis 7,8) . It has been reported that α 1 -protease inhibitor (α 1 -PI), an endogenous NE inhibitor, is inactivated by neutrophil -derived reactive oxygen species (ROS) 9) , resulting in attenuation of the NE inhibitory activity of α 1 -PI and a consequent increase in NE activity.…”
Section: Introductionmentioning
confidence: 99%